Subiectul III, ex.1.c.

Se consideră funcţia \(f :\mathbf R\rightarrow \mathbf R, f(x) = e^x - x -10\) .
Demonstraţi că \(e^{x^3}\geq (x+1)\left( x^2-x+1\right)\), pentru orice număr real \(x\) .
Soluţie. \begin{align} &\cssId{Step1}{Tabelul\;de\;variaţie\;al\;funcţiei\;}\\ &\cssId{Step2}{f'(x)=0\Rightarrow e^x-1=0\Rightarrow e^x=1\Rightarrow x=0}\\ &\cssId{Step3}{\begin{matrix} \;\;\;\;\;\;x \mid & -\infty\;\;\;\;\;\;\;\;\;\;\;\; &0\;\;&\;\;\;\;\;\;\;\;\;\;\;\;\;\;+\infty \\ \hline f'(x)\mid & -----&0\;\;&+++++ \\ \hline \;f(x)\mid&\searrow &min&\nearrow \end{matrix}\\}\\ &\cssId{Step4}{x=0\;este\;punct\;de\;minim\;\Rightarrow f(x)\geq f(0)=-9,\forall x\in \mathbf R}\\ &\cssId{Step5}{\Rightarrow f(x^3)\geq -9}\\ &\cssId{Step6}{\Rightarrow e^{x^3}-x^3-10\geq -9}\\ &\cssId{Step7}{\Rightarrow e^{x^3}\geq x^3+10-9}\\ &\cssId{Step8}{\Rightarrow e^{x^3}\geq x^3+1}\\ &\cssId{Step9}{\Rightarrow e^{x^3}\geq (x+1)(x^2-x+1),\forall x\in \mathbf R.}\\ \end{align}